LB19. Progress Toward a Vaccine for Maternal Immunization to Prevent Respiratory Syncytial Virus (RSV) Lower Respiratory Tract Illness (LRTI) in Infants. (26th November 2018) - Fries, Louis; Thomas, D Nigel; Smith, Gale; Plested, Joyce; Piedra, Pedro; Patel, Nita; Cho, Iksung; Glenn, Greg
Abstract: Background: RSV is the leading cause of infant LRTI and hospitalization worldwide. The greatest burden of severe disease is in term infants <5 months old. Novavax is developing an aluminum-adjuvanted RSV F nanoparticle vaccine for use in the third trimester of pregnancy, with the goal of preventing medically significant infant RSV LRTI in the first 3–6 months of life via transplacental transfer of maternal antibodies. Method: After dose-finding studies in 1, 050 women, we studied vaccine safety and immunogenicity in a Phase 2 trial in 50 healthy third trimester pregnant women. Safety was assessed in mothers and infants, focusing on pregnancy and peri-partum outcomes. We measured binding and functional RSV antibodies in mothers at baseline, day 14, delivery, and days 35 and 180 post-partum, in cord blood, and in infant sera on days 14, 35, 60, and 180 of life. Anti-F antibody specificities were probed with biolayer interferometry and monoclonal antibodies (mabs) to known epitopes. Result: In Phase 2, RSV F nanoparticle vaccine was immunogenic, safe, and well-tolerated in pregnant women. Anti-F IgG and neutralizing antibodies were elicited. Increases in antibodies competitive with mabs to neutralizing epitope sites Ø, VIII, II, and IV, and also the p27 domain displayed by the pre-fusogenic F protein, were present in maternal and infant sera of vaccinated subject pairs. Transplacental transfer of RSV antibodies was more efficient (110 to 120%) in women immunized >30 days before delivery compared with those vaccinated later; RSV antibody t 1/2 ranged from 30 to 41 days in infants. We have subsequently enrolled 4, 636 pregnant women and their infants in a global observer-blind, randomized, placebo-controlled Phase 3 trial assessing efficacy against medically significant RSV LRTI. In November 2017, an informational analysis performed by an independent statistician, the sponsor remaining blinded, yielded a posterior probability of ≥90% that efficacy was >0%. Conclusion: RSV F nanoparticle vaccine is immunogenic in pregnancy, and neutralizing antibodies, including those competing for pre-and post-fusion F epitopes, are transferred efficiently transplacentally. An analysis of Phase 3 efficacy against medically signifcant infant RSV LRTI is projected for Q1, 2019. Disclosures: L. Fries, Novavax: Employee and Shareholder, Salary. D. N. Thomas, Novavax: Employee, Salary. G. Smith, Novavax: Employee and Shareholder, Salary. J. Plested, Novavax: Employee, Salary. P. Piedra, Novavax: Collaborator, Consultant, Research Contractor and Scientific Advisor, Consulting fee, contract fees for immunologic assays and Research support. N. Patel, Novavax: Employee and Shareholder, Salary. I. Cho, Novavax: Employee and Shareholder, Salary. G. Glenn, Novavax: Employee and Shareholder, Salary.